Uncorking the limitation—improving dual tasking using transcranial electrical stimulation and task training in the elderly: a systematic review - Jiang, Yong; Ramasawmy, Perianen; Antal, Andrea (Frontiers in Aging Neuroscience, 2024)
With aging, dual task (DT) ability declines and is more cognitively demanding than single tasks. Rapidly declining DT performance is regarded as a predictor of neurodegenerative disease. Task training and non-invasive transcranial electrical stimulation (tES) are methods applied to optimize the DT ability of the elderly. A systematic search was carried out in the PUBMED and TDCS (transcranial direct current stimulation) databases, and a qualitative analysis was conducted in 56 included studies. Aiming to summarize the results of studies that implemented tES, task training, or the combination for improving DT ability and related performance changes in healthy elderly and geriatric patients. For different approaches, the training procedures, parameters, as well as outcomes were discussed. Task training, particularly cognitive-motor DT training, has more notable effects on improving DT performance in the elderly when compared to the neuromodulation method. Anodal tDCS over the left dorsolateral prefrontal cortex (L-DLPFC), or its combination with task training could be promising tools. However, additional evidence is required from aged healthy people and patients, as well as further exploration of electrode montage. Introduction Walking while answering the phone, talking while preparing a meal, or texting on the bus while maintaining a standing balance, dual task (DT) happens frequently in day-to-day life. Compared with performing one task in isolation, carrying out concurrently two tasks can deteriorate mutual performance, as the cognitive system has a limited capacity for attending to several attentiondemanding channels simultaneously (Navon and Gopher, 1979). Potential factors affecting DT capacity in old adults were discussed in previous studies. It has been identified that attention as well as execution factors are the most critical predictors of DT performance, and aging-induced decline in these factors is closely related to the increased risk of falls and impaired cognition in the elderly (